Produção acadêmica sobre cultura organizacional em escolas de educação básica no Brasil de 2006-2020 - Yamazato, Marcelo Oda (Universidade Federal de São Carlos, 2021)
This dissertation derives from an investigation which was developed within the Study and Research Group on School Organization: Democracy, Human Rights and Principals’ development - DEFORGES. Organizational culture in Brazilian schools was its theme, having as its problem the following question: how is the academic production on organizational culture configured in basic education schools in Brazil? Thus, the general objective was to understand the theoretical and methodological approaches to the subject in the articles, dissertations and thesis that constitute this production and the specific objectives were to map research on this theme from 2006 to 2020, systematizing its theoretical references, methodological procedures, and conclusions, and to analyze the theoretical matrices referring to culture in these studies. The methodological approach was the bibliographic one, carried out on SciELO and CAPES Theses and Dissertations Repository digital databases. Critical theoretical framework guided the results analysis, which indicated that: the most used research design was the case study; the most used data collection instrument was document analysis followed by semi-structured interviews; the most investigated level of education was elementary school followed by high school in public municipal and state institutions. The references of Edgar Schein, António Nóvoa and Heloísa Lück also stood out. In addition, it was possible to observe that the organizational culture was worked in relation to several topics, the most frequent being school management, change processes, democratic management, and school performance. In most of the works, the study of organizational culture was developed to analyze the school reality, relating to, and facilitating investigations on several other topics, being able to show the subjects' autonomy and their possibilities of construction and reconstruction of organizational culture. It was concluded that organizational culture is a concept that can contribute to research on schools, especially those that seek to investigate their dynamics, functioning and relationships. In addition, it became evident that organizational culture in the context of Brazilian education is still a yet to be explored theme that has the potential to subsidize school administration in its daily practices.
Academic production on organizational culture in basic education schools in Brazil from 2006-2020
Keywords: Cultura organizacional; Administração escolar; Educação; Organização escolar; Organizational culture; School administration; Education; School organization; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL